2009
DOI: 10.1089/jwh.2008.0985
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Home Pregnancy Test Instructions

Abstract: Readability and formatting characteristics of most HPT instructions do not meet recommended criteria for compliance with plain language guidelines. These findings underscore the need for improved instructions and ultimately improving patients' ability to use HPTs and interpret results with accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Fonts of open letter types and interline spacing equal or larger than 2 are better readable compared to fonts of closed letter types and interline spacing smaller than 2, especially at larger text columns. For patient education materials and health instructions, font sizes of 12 or larger are recommended [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Fonts of open letter types and interline spacing equal or larger than 2 are better readable compared to fonts of closed letter types and interline spacing smaller than 2, especially at larger text columns. For patient education materials and health instructions, font sizes of 12 or larger are recommended [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Implementation of the FDA-approved athome pregnancy test provides an instructive example. Although these tests have been sold for over 40 years, and clinical trials research suggested at-home pregnancy tests could be implemented with high fidelity, subsequent studies provide convincing evidence that various population segments continue to have significant challenges with implementing at-home pregnancy tests [43][44][45][46]. Both SITs and at-home pregnancy testing require that program features fit the diverse populations that may use them, and those at highest risk may have characteristics (low income, poor education) that require different instructional strategies.…”
Section: Overviewmentioning
confidence: 99%
“…Font size was measured in Cicero as the ‘kp’ distance. For health instructions in general, font sizes >12 are recommended, interline spacing ≥2 and fonts of open letter types [16]. The readability level was expressed as Flesh Kincaid grade level.…”
Section: Methodsmentioning
confidence: 99%
“…The readability level was expressed as Flesh Kincaid grade level. There are no criteria of readability levels for IFUs but for patient education files, a level ≤6 th grade is recommended [16].…”
Section: Methodsmentioning
confidence: 99%